BILATERAL RHEGMATOGENOUS RETINAL DETACHMENT IN A YOUNG ADULT WITH NEUROFIBROMATOSIS 1 - Tanveer, Shafiq; Peters, Khushbakht H; Bibi, Hafsa; Tahir, Asna; Shahnawaz, Ghazala (Indonesian Vitreoretinal Society, 2024)
Introduction: Neurofibromatosis (NF) is a set of phakomatoses involving genetic disorders, commonly associated with nerve sheath tumor development. NF1 affects various bodily systems, with ocular signs like optic pathway gliomas and Lisch nodules. Case Presentation: We present a unique case of a 33-year-old man with a classic presentation of neurofibromatosis type 1 (NF1), who sought a routine ocular examination without any specific complaints. The detailed ocular examination revealed oculus uterque (OU) retinal detachments (RD) with superonasal retinal cysts and inferior retinal dialysis in the ocular RD in NF1 patients, distinct from the previously documented cases of unilateral RD with ora serrata dialysis in NF1 patients. Discussion: This case report contributes to the expanding body of literature on atypical ophthalmic presentations in NF1 patients and suggests a potential link between suboptimal fibroblastic function in NF1 and the development of retinal complications, proposing a mechanism involving faulty collagen production and subsequent vitreous base avulsion leading to retinal dialysis and detachment. Conclusion: This case underscores the significance of thorough routine ocular examination in NF1 patients, emphasizing the need for a heightened suspicion of unusual ocular manifestations.